PEMBERDAYAAN MASYARAKAT LOKAL DALAM MENDUKUNG PENGEMBANGAN DESA WISATA DUDA TIMUR, KARANGASEM, BALI - Putu Guntur Pramana Putra; I Nengah Subadra; Ni Nyoman Rusmiati; Ni Luh Sili Antari; I Dewa Ayu Tita Permata Tabita; I Gusti Agung Sasih Gayatri; I Wayan Arta Artana (Synergy and Society Service, 2023)
East Duda Village is a village located in Selat District, Karangasem Regency, Bali which is culturally and spiritually filled with the potential for plantations, waterfalls, rolling hills and other tourist attractions. Most of the people make their living as farmers, especially as salak farmers. Apart from that, the economic growth of East Duda Village is also influenced by the tourism sector. The aim of this service is to empower local communities in managing the potential of their villages to support tourism. The implementation methods used in this community service are discussion, interviews, presentations and community service methods. The results of the community service carried out are producing village promotional videos, teaching children in elementary schools, entrepreneurship seminars for MSMEs, Cooking Classes for PKK mothers, Launching Arak Poleng and Community Service in the village environment.